Therapeutic strategies to overcome EGFR mutations as acquired resistance mechanism in ALK-rearranged non-small-cell lung cancer: Case Reports - Michaux, Lionel; Perrier, Alexandre; Mehlman, Camille; Alshehhi, Hussa; Dubois, Antonin; Lacave, Roger; Coulet, Florence; Cadranel, Jacques; Fallet, Vincent (Frontiers in Oncology, 2023)
Introduction ALK tyrosine kinase inhibitors (ALK TKIs) have improved prognosis in ALK-rearranged (ALK+) non-small-cell lung cancer (NSCLC). However, drug resistance mechanisms occur inevitably during the course of treatment leading to disease progression. Activation of epidermal growth factor receptor (EGFR) bypass signaling pathway is an uncommon cause of acquired resistance to ALK TKIs. Method We present two patients with EML4-ALK rearranged NSCLC, developing an acquired EGFR resistance mutation after receiving multiple lines of ALK TKIs. Results While preclinical models have showed encouraging data, there is a critical need for clinical studies on treatment strategies to overcome this drug resistance. Three real-life therapeutic approaches were used in this report: i) using brigatinib, an inhibitor targeting both ALK and EGFR tyrosine kinases; ii) combining two ALK TKIs together; and iii) delivering doublet platinum chemotherapy. In case 1, time to treatment failure (TTF) was 9.5 months with brigatinib; in case 2, TTF was 10 months with combined TKIs (osimertinib and brigatinib), whereas TTF with chemotherapy was only 2 months. Tolerability profile TKIs combotherapy was acceptable. Conclusion These case reports underline the therapeutic complexity of EGFR-acquired resistance mutation in ALK+ NSCLC and offers some leads to solve this real-life clinical challenge.